2016
DOI: 10.1111/adb.12348
|View full text |Cite
|
Sign up to set email alerts
|

Frontostriatal circuits, resting state functional connectivity and cognitive control in internet gaming disorder

Abstract: Converging evidence has identified cognitive control deficits in internet gaming disorder (IGD). Recently, mounting evidence had revealed that resting state functional connectivity (RSFC) and structural connectivity of frontostriatal circuits could modulate cognitive control in healthy individuals. Unfortunately, relatively little is known about the thoroughly circuit-level characterization of the frontostriatal pathways (both the dorsal and ventral striatum) during resting-state and their association with cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
110
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 50 publications
9
110
2
4
Order By: Relevance
“…IA is a risk correlated with suicidal behavior [5254], and even its limitation observed in the adolescent group was consistent with our findings, which can be explained by decreased cognitive control seen in neuroimaging studies in the IA group [42, 55]. On classifying suicide-related behavior into three different characteristics such as suicidal ideation, plan, and previous attempt, the current study showed that the IA with sleep problem group had more tendency for suicide plan and attempt, while the IA without sleep problem group had more tendency for suicide ideation and plan.…”
Section: Discussionsupporting
confidence: 89%
“…IA is a risk correlated with suicidal behavior [5254], and even its limitation observed in the adolescent group was consistent with our findings, which can be explained by decreased cognitive control seen in neuroimaging studies in the IA group [42, 55]. On classifying suicide-related behavior into three different characteristics such as suicidal ideation, plan, and previous attempt, the current study showed that the IA with sleep problem group had more tendency for suicide plan and attempt, while the IA without sleep problem group had more tendency for suicide ideation and plan.…”
Section: Discussionsupporting
confidence: 89%
“…It is one of the brain regions where IGD-associated abnormalities have been widely reported in molecular (46), structural (47, 48), and functional studies (17). For example, young adults with internet addiction exhibit reduced dopamine D2 receptor availability in the bilateral dorsal caudate, and the severity of internet addiction measured by IAT scales is negatively associated with dopamine D2 receptor availability in the left caudate (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, young adults with internet addiction exhibit reduced dopamine D2 receptor availability in the bilateral dorsal caudate, and the severity of internet addiction measured by IAT scales is negatively associated with dopamine D2 receptor availability in the left caudate (46). Also, IGD individuals appear to have increased gray matter volume in the caudate, along with impaired cognitive control performance (47). Dong et al (17) have reported reduced caudate activation in individuals with internet addiction during decision making in the context of “continuous” wins, suggesting insufficient attention to previous behavior selections and their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies revealed that weeks to months of video game training altered functional activities, resting‐state functional connectivity and gray matter volumes/cortical thickness of the DLPFC and other brain regions such as the orbitofrontal cortex (OFC) and striatum . OGA and general internet addiction were frequently reported to be associated with functional and structural abnormalities in the DLPFC, OFC and anterior cingulate, as well as the WM tracts connecting to these regions .…”
Section: Introductionmentioning
confidence: 99%